Mary Poppins - Travers, P. L. (Pamela Lyndon), 1899-1996 (Mary Poppins., 1997)
An extraordinary English nanny blows in on the East Wind with her parrot-headed umbrella and magic carpetbag and introduces her charges, Jane and Michael, to some delightful people and experiences.